A study on acute kidney injury in patients with acute coronary syndrome preliminary data: a single-center experience - Chang, CY; Chan, CE; Muhd Syafiq, MI; Fariz Safhan, MN; Wan Ali, Wan Ahmad Syahril Rozli; Ahmad, MK; Seman, MR (Elsevier, 2017)
Introduction: Acute kidney injury (AKI) is increasingly being seen in patients presented with acute coronary syndrome (ACS). The reported incidence of ACS-associated AKI is extremely heterogeneous ranging from 5% to 55%, depending on clinical setting and investigated pop- ulation. The occurrence of AKI has been shown to be adversely affecting the patients’ clinical outcome and mortality. Objective: The aim of this study is to describe the incidence of AKI in patients presented with ACS and to evaluate its associated outcome. Methodology: Patients admitted for ACS from 1stMarch 2017 to 28th February 2018 will be enrolled into this study. Subjects will be grouped into either AKI group or non-AKI group based on AKIN criteria. Patients with AKI will subsequently be followed up regularly at 3 months interval for 1 year to monitor the outcome of AKI. Patients’ de- mographic data, comorbidities, medication use, serum urea and serum creatinine on admission and 48 hours and other blood investigations were recorded. The data obtained from the first two months were extracted from analysis. Results: There were 22 patients enrolled in this preliminary analysis. The mean age of subjects was 54.8 (11.4) years old. Eleven (50%) patients were diagnosed with unstable angina, followed by 7 (32%) patients with STEMI and 2 (9%) patients with NSTEMI. Three patients (13.6%) were found to have AKI in which 2 (66.7%) were in AKIN I and 1 (33.3%) was in AKIN 3. Dialysis support was initiated for the patient with AKIN 3. The AKI group had higher level of serum creat- inine on admission which was 268.3 umol/L (134.9) as compared to non- AKI group of 141.4 umol/L (91.3) (p 1⁄4 0.047). There was no significant association between occurrence of AKI and patients’ age, gender, comorbidities (i.e. diabetes mellitus, hypertension and stroke), previous usage of medications (i.e. ACEi/ARB or diuretics), and level of haemo- globin or albumin.